Performance-Based Accountability and Teacher Emotions: Role of Zhongyong Thinking - Zhang, Ying; Tsang, Kwok Kuen (Frontiers in Psychology, 2021)
Teachers’ emotions may be affected by structural reforms of education that emphasizes performance-based accountability (PBA) and by individual psychological processes like thinking style, but there is a lack of research concerning the relationship between the three factors. In this study, thus, we attempted to test the influence of PBA on teacher emotions and to examine whether the relationship was moderated by a zhongyong thinking style in a Chinese context. A sample of 402 primary and secondary schoolteachers from Hubei, Liaoning and Beijing in China participated in this study. Structural equation modeling was applied to develop moderation models. The results demonstrated that PBA is a singificant factor with respect to teachers’ joy, sadness/frustration, anger, and fear, as related to their job of teaching, but not love of their profession. Moreover, the zhongyong thinking style may moderate the relationship between PBA and joy.